Cost‐effective Purification of Membrane Proteins using a Dual‐detergent Strategy. Issue 6 (17th June 2022) - Brahma, Rupasree; Raghuraman, H.
Abstract: Understanding the mechanisms of membrane protein function is critical for biomedical research and drug discovery as membrane proteins constitute ∼30% of the proteins encoded by the genomes of both lower and higher organisms and are targets for two‐thirds of approved drugs worldwide. Significant progress has been made in engineering host expression systems for large‐scale production of membrane proteins and in determining their three‐dimensional high‐resolution structures. Despite these efforts, the study of membrane proteins at the atomic level is challenging due to poor expression and extraction, low yields of functional protein, and the complexity and heterogeneity of source membranes. Structural and spectroscopic studies of any membrane protein require that the protein be extracted from its native membranes into a membrane‐mimetic stable environment, which is often achieved by the use of detergents. Unfortunately, there is no magic detergent that can extract all membrane proteins and successful extraction often requires a thorough screen of detergents. Furthermore, membrane protein purification in general and the detergents used are very expensive, which puts a financial constraint on sophisticated membrane protein studies. To overcome this hurdle, a dual‐detergent strategy has recently been developed and successfully applied to purify various classes of pure, stable, and functionally relevant membrane proteins in a cost‐effective manner. This strategy uses an inexpensive detergent for solubilization of the desired protein from membranes and a second detergent during protein purification. In the Basic Protocol, we describe the dual‐detergent strategy to significantly reduce the overall purification cost of a bacterial membrane protein using the magnesium ion channel MgtE as an example. Support Protocols are also provided for selecting a suitable E. coli strain for protein expression and the optimal detergent(s) for membrane protein solubilization. © 2022 Wiley Periodicals LLC. Basic Protocol : Expression, membrane solubilization, and cost‐effective purification of MgtE Support Protocol 1 : Selecting a suitable E. coli strain for optimal protein expression Support Protocol 2 : Identification of suitable detergents for membrane protein solubilization